"INSTITUSI KEUANGAN SEBAGAI CERMIN MASYARAKAT: KAJIAN SOSIOLOGIS PERBANKAN KONVENSIONAL DAN ISLAM" - raihana, fauziah (Samawa (Sakinah, Mawaddah Warahmah), 2025)
This study aims to examine how financial institutions, particularly conventional and Islamic banking in Indonesia, reflect social dynamics, cultural values, and religious preferences within society. The main issue addressed is how both individual and collective choices regarding types of banking are influenced by social constructs, levels of religiosity, and perceptions of justice and economic ethics. Using a qualitative approach through literature review and semi-structured interviews with banking customers and practitioners in several cities across Indonesia, this research highlights differences in motivation and perception between users of the two banking systems. The findings indicate that Islamic banking is more commonly chosen by individuals with strong adherence to religious values and ethical financial principles (muamalah), whereas conventional banking tends to dominate among urban communities with a pragmatic and efficiency-oriented mindset. Additionally, a new trend of "hybrid behavior" is emerging, where individuals utilize both systems simultaneously depending on their needs. This suggests that banking institutions function not only as economic tools but also as mirrors of social complexity and the values embedded in modern society.